The Ghost Club, 1882–1936: Strong Bonds, Weak Connections - Luckhurst, Roger (Aries, 2022)
The Ghost Club was founded to discuss matters spiritual, psychic and occult in 1882 by Spiritualist William Stainton Moses and mystic Alfred Alaric Watts. It was intended as a club ruled by a gentleman’s code of honour—with all matters discussed kept strictly confidential. While maintaining secrecy, it also obsessively minuted and documented its discussions, leaving behind thousands of pages of records that have yet to be properly investigated, owing to conditions around their use. This essay is an attempt to examine the importance of the Club, and how it might readjust our understanding of the networks of the London occult in the late-Victorian and Edwardian eras.